Incidence and prognostic factors of ataxia in children with posterior fossa tumors. Issue 3 (21st August 2018) - Hartley, Helen; Pizer, Barry; Lane, Steven; Sneade, Christine; Williams, Rebecca; Mallucci, Conor; Bunn, Lisa; Kumar, Ram
Abstract: Background: There is minimal literature specific to motor outcomes in children with posterior fossa tumors (PFTs) despite ataxia being a significant problem in this group. This study aims to report children's physical outcomes following management of PFT and determine which factors affect severity of ataxia and functional limitations. Methods: Forty-two children aged between 5 and 17 and between 1 and 4 years following surgery for PFT were assessed using the Scale for the Assessment and Rating of Ataxia (SARA), the Brief Ataxia Rating Scale (BARS), and the mobility Pediatric Evaluation of Disability Inventory (PEDI) subscale to determine prevalence and severity of ataxia and a measure of physical function. Analysis was undertaken comparing impact of tumor location, tumor histology, adjuvant treatment, age at diagnosis, presence of preoperative ataxia, and presence of cerebellar mutism syndrome (CMS) on ataxia and physical function scores. Results: Seventy-one percent of children demonstrated a SARA and BARS score greater than 2. A total of 48% of children had a PEDI-m score greater than 90. There was no correlation between age at diagnosis or preoperative ataxia and assessment scores. There was a significant difference in SARA/BARS and PEDI-mobility scores depending on tumor histology, tumor location, and presence of CMS. Conclusions: A high proportion of children (>1 year) following surgery for PFT continue to present with ataxia. Higher ataxia and lower physical function scores were demonstrated in children with medulloblastoma and midline tumors and those diagnosed with CMS. The high prevalence of ataxia demonstrates the need for further research regarding rehabilitation management in this population.